An advanced solution to boost sun-to-electricity efficiency of parabolic dish. (1st December 2016) - Giostri, Andrea; Macchi, Ennio
Highlights: A model to study parabolic dish coupled with regenerative gas turbine is proposed. Adoption of ceramic expander technology is able to boost parabolic dish efficiency. A solar to electricity efficiency of 26.48% is obtained. Abstract: This paper investigates the coupling of parabolic dish concentrator with air micro gas turbine engine (net power output equal to 32.9 kWel ). With the aim of increasing the conversion efficiency of the incoming solar radiation, a high temperature system (up to 1100 °C) has been considered: this solution implies the adoption of a ceramic expander coupled with a high temperature indirectly-irradiated solar receiver. A flexible Matlab® suite has been developed for the plant sizing and for the part-load simulation; in addition, the model is able to handle general solar field configurations through the computation of reciprocal shading effect. The obtained yearly sun-to-electric efficiency (26.48%) reveals the energetic advantage over other CSP technologies that can mitigate the technological issues and consequently higher investment cost, related to high operating temperatures. The potential of a hybrid version of the dish is also discussed.